PCR-Detection of Coxiella burnetii in Ticks Collected from Sheep and Goats in Southeast Iran - SR Nourollahi Fard; M Khalili (Tehran University of Medical Sciences, 2011)
Background: There is a little data on Coxiella burnetii (Q fever agent) in Iran. Ticks may play a significant role in the transmission of C. burnetii among animals. The aim of this study was to use polymerase chain reaction for the detection of C. burnetii in ticks collected in Southeast Iran. Methods: One hundred and sixty ticks were collected from domestic animals in three localities of Kerman Province, Southeast Iran from November to June 2009. The collected ticks were divided into 35 pools and examined by Trans-PCR for C. burnetii. Results: Three pools, each consisting of five female of Hyalomma anatolicum anatolicum and one pool (6 ticks) of Rhipicephalus sanguineus ticks collected from goats and sheep were found to be positive by Trans-PCR. Conclusion: This paper documents the first molecular detection of C. burnetiiin ticks, which shows their role as putative vectors and reservoirs for this pathogenic agent.